BPTF Drives Gastric Cancer Resistance to EGFR Inhibitor by Epigenetically Regulating the C‐MYC/PLCG1/Perk Axis - Fangyuan Li; Junxian Yu; Tao Pan; Haoran Feng; Jianfang Li; Beiqin Yu; Zhiyuan Fan; Qingqing Sang; Mengdi Chen; Mingde Zang; Junyi Hou; Xiongyan Wu; et al. (Advanced Science, 2023)
Abstract Erlotinib, an EGFR tyrosine kinase inhibitor, is used for treating patients with cancer exhibiting EGFR overexpression or mutation. However, the response rate of erlotinib is low among patients with gastric cancer (GC). The findings of this study illustrated that the overexpression of bromodomain PHD finger transcription factor (BPTF) is partially responsible for erlotinib resistance in GC, and the combination of the BPTF inhibitor AU‐1 with erlotinib synergistically inhibited tumor growth both in vivo and in vitro. AU‐1 inhibited the epigenetic function of BPTF and decreased the transcriptional activity of c‐MYC on PLCG1 by attenuating chromosome accessibility of the PLCG1 promoter region, thus decreasing the expression of p‐PLCG1 and p‐Erk and eventually improving the sensitivity of GC cells to erlotinib. In patient‐derived xenograft (PDX) models, AU‐1 monotherapy exhibited remarkable tumor‐inhibiting activity and is synergistic anti‐tumor effects when combined with erlotinib. Altogether, the findings illustrate that BPTF affects the responsiveness of GC to erlotinib by epigenetically regulating the c‐MYC/PLCG1/pErk axis, and the combination of BPTF inhibitors and erlotinib is a viable therapeutic approach for GC.